The Effect Of Learning Styles And Self-Confidence On Students' Understanding of The Concept of Relational Presentation - Huri Suhendri; Lasia Agustina; Dahroni Dahroni; Almaida Garudea Putri; Yulianah Yulianah (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to analyze the influence of students’ learning styles and self-confidence on their conceptual understanding of relation representation in mathematics at SMP Negeri Satu Atap 01 Ciseeng. The preliminary data showed that 65% of students had not achieved mastery learning. A qualitative descriptive survey method was applied involving 48 eighth-grade students. Data were collected through interviews, classroom observations, and document analysis, and were analyzed using Miles and Huberman’s interactive model with triangulation for data validation. The findings reveal that visual learning style is dominant (42%) and produces the highest average score (82). Most students’ self-confidence is at the moderate level (60%), while those with high self-confidence achieve better performance (85). The combination of visual learning style and high self-confidence results in the highest conceptual understanding score (86). This study confirms the relevance of differentiated instruction and Deep Learning models in mathematics education. The findings imply the need for adaptive teaching strategies that accommodate students’ diverse learning styles while fostering self-confidence.